The SE Area of the Central Baths: from Residential Area to Pars Publica (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
Since 2001, the archaeological excavation of the University of Milan has been taking place in the so-called “E Area”, in the central area of the ancient Nora. This area shows a complex stratigraphic sequence with public buildings (the most important is the so-called Central Baths) and private houses. After the first analysis, the late roman city (after 450 AD) has been discovered: many houses (domus) dated at II-III century AD, with polychrome marbles, and big publics buildings with decorated floor have been individuated. Since 2008, the excavations have been taking place in the complex of the Central Baths, focusing in particular on the public accesses of the Severian Baths, analyzing also the previous phases characterized by a private use of the complex.
Keywords: Baths; Nora; room of service; pars publica; pars privata